Hardened faecal pellets as a significant component in deep water, subtropical marine environments. (13th March 2019) - Deik, Hanaa; Reuning, Lars; Petrick, Benjamin; Takayanagi, Hideko
Abstract: Non‐skeletal carbonate grains are classically interpreted to form in shallow, tropical environments. Peloids deposited in deep, subtropical marine conditions are poorly studied. IODP site U1460 on the subtropical Carnarvon Ramp (Southwest Shelf of Australia) recovered a nearly continuous Pliocene to Recent record of outer shelf and slope sediments. The relative abundance of peloids varies between 0% and 67% of the fine to medium sand fraction, and contributes on average 4% of all grains. The origin and composition of these peloids were investigated using scanning electron microscopy equipped with an energy‐dispersive X‐ray spectrometer, light microscopy, X‐ray diffraction and stable isotope analysis. The peloids have a uniform size and shape and are interpreted as faecal pellets. They are mainly composed of skeletal fragments such as ascidian spicules, planktic foraminifera and sponge spicules in a mud‐sized matrix containing abundant coccolith plates. Mineralogical analysis show that the pellets consist of aragonite, calcite and dolomite. The pellets have an identical mineralogical composition and skeletal assemblage as the surrounding matrix, indicating that they have formed in situ. They occur more abundantly during interglacials when the site was situated in deeper waters below the swell wave base, presumably because the pellets were protected from disintegration and therefore available for cementation. The presence of framboidal pyrite within the pellets indicates bacterial sulphate reduction (BSR). The reduction of iron by hydrogen sulphide produced during BSR decreases the pH and likely explains the observed aragonite dissolution. Aragonite dissolution likely increases the alkalinity, and in consequence causes the precipitation of calcite and dolomite cements. It is suggested here that pellets are hardened due to this early cementation close to the sea floor increasing the potential for preservation in the fossil record. Abstract : The peloid content in the deep‐ and cool‐water carbonates is higher than or similar to many tropical shallow water carbonates from the Indo‐Pacific region. They are hardened due to seafloor early cementation by calcite which making them available in the fossil record.